THE ASSESSMENT OF PATIENTS WITH NON-EROSIVE GASTROESOPHAGEAL REFLUX DISEASE BY USING THE BRAVO® PH MONITORING SYSTEM - Gok, Mehmet; Gencdal, Genco (Sanamed, 2022)
Background and aim: Gastroesophageal reflux disease (GERD) is a common disease in the world. GERD is always treated with drugs. The Bravo® wireless pH monitoring system is a good technique. The Bravo® may affect increasing the specificity and sensitivity in the diagnosis of GERD with its 48-hour recording feature. In this study, we aimed to assess the diagnostic performance of the Bravo® pH monitoring system in patients with non-erosive GERD. Materials and Methods: Patients with non-erosive reflux disease (normal endoscopy) whose symptoms persisted after PPI treatment (at least two months) were included in the study. All patients had upper gastrointestinal system endoscopies performed in our clinic between January 2013 and December 2019. All patients had a 48-hour Bravo® wireless pH monitoring record. Results: Twenty-three patients (M: 18 (78.3%; Age:35.7±11) were included in the study. All patients completed the 2-day recording protocol. During and after the procedure, no patient showed any adverse effects of the Bravo® procedure. We diagnosed GERD in 13 of 23 patients by Bravo® capsule. According to the Bravo® pH-meter recordings; Total time pH<4 (minute) was 187±190, the total number of refluxes was 90±61, the percentage of time with pH<4 was 7.1±7.22, the number of long reflux events were 8.1±8, the duration of the longest reflux episode during pH<4 (minute) was 31±49, the Demeester score was 20.8±19.3 detected. Conclusion: Based on the results of the current study, the Bravo® pH monitoring system is a practical and effective diagnostic technique for non-erosive GERD. Further prospective studies would be useful for comparing the differences between 24-hour and 48-hour pH recording results.